Studies of Small-intestinal Mucosa with the Scanning Electron Microscope. Issue 5623 (12th October 1968) - Marsh, M. N.; Swift, J. A.; Williams, E. D.
Abstract : Preliminary observations indicate that scanning electron microscopy is a useful method for studying the surface of the small intestine.